Perkembangan Politik Hukum Peradilan Adat - Herlambang Perdana Wiratraman (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2018)
AbstractThe politics of decentralization after Suharto provided more space in the discourse of adat justice in Indonesia. The problem is that the legal political process does not stand in empty space. Adat justice issues in the political system that regulates political-economic authority, which is supported by the character of the persistence of a network of oligarchs, massive destruction of destructive natural resources, and corrupt and feudalistic bureaucracies. This article encourages local democracy that fosters broad community participation, including encouraging the work of adat justice, has paralyzed the empowerment of the judiciary itself, so that the legal politics of adat justice openly triggers a symbol of certain feudalism protection.IntisariKonteks politik desentralisasi pasca Suharto memberi ruang lebih dalam diskursus peradilan adat di Indonesia. Masalahnya, proses politik hukum itu tak berdiri di ruang kosong. Peradilan adat berinteraksi dalam sistem politik yang menampilkan kuasa ekonomi-politik, yang dipenuhi dengan karakter bertahannya jaringan oligarki, eksploitasi sumberdaya alam yang masif nan merusak, serta birokrasi yang korup dan feodalistik. Artikel ini memperlihatkan demokratisasi lokal yang menumbuhkan partisipasi masyarakat secara luas, termasuk mendorong bekerjanya mekanisme peradilan adat, telah melumpuhkan keberdayaan peradilan itu sendiri, sehingga politik hukum peradilan adat, secara bertahap melahirkan simbolisasi kuasa feodalisme tertentu.